Impact of pregnancy on antibody response to COVID-19 vaccine - Majumder, Dipika; Das, Tripti Rani; Sharmin, Riffat Ara; Chowdhury, Tanzina Iveen; Jahan, Noor; Tamanna, Tabassum; Islam, Fahmida; Nazneen, Fahmida (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Vaccination during pregnancy is a common and recommended practice to prevent maternal and infant morbidity from many infectious diseases. Likewise, pregnant women should be vaccinated against COVID-19 to protect themselves and their expectant children. The immune system is known to undergo alterations during pregnancy. Therefore, the present study was undertaken to determine the impact of pregnancy on antibody response in Bangladeshi pregnant women following two doses of the COVID-19 vaccine. Methods: This cross-sectional study was conducted in the department of obstetrics and gynecology, Bangabandhu Sheikh Mujib medical university (BSMMU), Dhaka, Bangladesh from April 2022 to March 2023. This study included COVID-19-vaccinated 25 pregnant and 25 nonpregnant women attending the outpatient department (OPD) of obstetrics and gynecology, of BSMMU. Results: The pregnant women were younger than the non-pregnant women. A few of the study subjects were hypertensive and/or diabetics and there was no difference between the study groups concerning hypertension and diabetes (p=0.500 and p=0.174 respectively). Over 20% of the study subjects were ever tested for COVID-19, but none were positive for COVID-19 infection. More than half of the subjects received Pfizer-BioNTech COVID-19 vaccination. In the majority of the pregnant and non-pregnant women, blood was collected after 6 weeks of the second dose of the vaccine. The IgG antibodies to SARS-CoV-2 were almost similar in both the study groups (15401.4 vs. 16575.6 AU/ml respectively) (p=0.742). Conclusions: This study found that pregnancy did not significantly impact the antibody response to COVID-19 vaccination. The study also concluded that pregnant women respond well to the COVID-19 vaccines, mounting strong immune responses with final titers being fairly comparable to those in non-pregnant women of reproductive age.